Adoption of climate-smart practices and its impact on farm performance and risk exposure among smallholder farmers in Ghana - Gazali Issahaku; Awudu Abdulai (Australian Journal of Agricultural and Resource Economics, 2019)
Increased climate variability during the last four decades has made the agricultural environment in many developing countries more uncertain, resulting in increasing exposure to risk when producing crops. In this study, we use recent farm-level data from Ghana to examine the drivers of individual and joint adoption of crop choice and soil and water conservation practices, and how adoption of these practices impacts on farm performance (crop revenue) and exposure to risks (skewness of crop yield). We employ a multinomial endogenous switching regression model to account for selectivity bias due to both observable and unobservable factors. The empirical results reveal that farmers' adoption of crop choice and soil and water conservation leads to higher crop revenues and reduced riskiness in crop production, with the largest impact on crop revenues coming from joint adoption. The findings also show that education of the household head, access to extension and weather information influence the likelihood of adopting these practices. Thus, enhancing extension services and access to climate information and irrigation can reduce gaps in adoption of soil and water conservation and crop choice, considered as climate-smart practices that will eventually improve crop revenues and reduce farmers' exposure to climate-related production risks.
Keywords: 330; Africa; climate-smart practices; farm performance; impact assessment; risk exposure